Sensitivity Analysis for Utility Maximization: A Study on Lagrange Multipliers and Commodity Coupons - Mohajan, Haradhan Kumar; Mohajan, Devajit (Journal of Economic Development, Environment and People, 2023)
In this study sensitivity analysis among Lagrange multipliers and commodity coupons are discussed with detail mathematical analysis. In economics, utility maximization method is essential for the increasing of the sustainable production and profit maximization. Two types of constraints, such as budget constraint, and coupon constraint are used to operate sensitivity analysis; consequently, two Lagrange multipliers are applied for the detail mathematical analysis.